ESTUDIO DE LA CONCENTRACIÓN DEL CARBONO EN SUELOS DE MANGLAR EN ECUADOR CONTINENTAL - Miranda Muñoz, Rodrigo Antonio. (2022)
Mangroves are halophytic woody plants found along subtropical and tropical coasts, which thanks to their root structure and high sedimentation rates, make their forests the largest blue carbon reservoirs in the world. In Ecuador they cover an area of approximately 1570 km² and have developed an important role in society, however, they have suffered great anthropogenic disturbances over time. The objective of this study is to analyze the carbon concentration in mangrove soils of continental Ecuador. The data from dasometry and soil sampling at different depth intervals were recorded at nine estuarine sites along the coast to determine the percentage of total carbon in mangrove soils. El Salado was divided into two zones, and was the only site where total organic carbon was estimated. Cayapas Mataje and Isla Bellavista had the highest total carbon values. There is a slight linear relationship between the Dasometric Index and the percentage of total carbon, which decreases as depth increases. The "El Salado" sites presented total organic carbon storage of 30.01 to 21.50 MgC/ha, even though they are a remnant of urban mangroves, they represent an important reservoir for carbon sequestration, so their conservation should be a priority